2020
DOI: 10.1080/14756366.2020.1819258
|View full text |Cite
|
Sign up to set email alerts
|

Novel temporin L antimicrobial peptides: promoting self-assembling by lipidic tags to tackle superbugs

Abstract: The rapid development of antimicrobial resistance is pushing the search in the discovering of novel antimicrobial molecules to prevent and treat bacterial infections. Self-assembling antimicrobial peptides, as the lipidated peptides, are a novel and promising class of molecules capable of meeting this need. Based on previous work on Temporin L analogs, several new molecules lipidated at the Nor and the C-terminus were synthesised. Our goal is to improve membrane interactions through finely tuning self-assembly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 23 publications
(63 citation statements)
references
References 53 publications
1
62
0
Order By: Relevance
“…It may be related to the decrease of the helical content; however, it could also be caused by the change of aggregation effects. Previous studies have shown that AMPs with strong antimicrobial activity are present as monomers in an aqueous solution and aggregate on the membrane to disrupt the bacterial cell membrane [ 40 , 41 ]. However, when the aggregation ability is too strong, they may start to aggregate before attaching on the cell membrane, suggesting that their potency to disrupt the cell membrane could be affected and reduced [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…It may be related to the decrease of the helical content; however, it could also be caused by the change of aggregation effects. Previous studies have shown that AMPs with strong antimicrobial activity are present as monomers in an aqueous solution and aggregate on the membrane to disrupt the bacterial cell membrane [ 40 , 41 ]. However, when the aggregation ability is too strong, they may start to aggregate before attaching on the cell membrane, suggesting that their potency to disrupt the cell membrane could be affected and reduced [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lipidation and glycosylation of molecules can be a modification of both natural and synthetic AMPs. Aliphatic chain in peptides modulates their hydrophobicity, tendency to self-assembly, while the possibility of action through an intracellular receptor is not excluded [ 67 , 68 , 69 , 70 ]. Glycated peptides also demonstrate greater biostability, the ability to self-assemble complex frameworks, and increase selectivity [ 71 , 72 ].…”
Section: Brief History Of Research Physicochemical Properties CLmentioning
confidence: 99%
“…Peptide 12 showed the same mechanism of action of linear peptide 9 , as elsewhere reported. 76 Peptide 12 caused a low leakage on LUVs mimicking the membrane of Gram-positive bacteria, whereas a strong leakage effect was observed on LUVs mimicking Gram-negative bacterial membranes. This finding is in line with the capability of the peptide to kill MRSA bacterial cells, as demonstrated by time kill assay ( Figure 7 ), and to reduce the viability of S. aureus and A. baumannii biofilms.…”
Section: Discussionmentioning
confidence: 94%
“…SUVs were prepared as reported: lipids (Gram-positive, DOPG/CL, 58/42 ratio in moles; Gram-negative DOPG/DOPE/CL, 63/23/12 ratio in moles) were dissolved in chloroform and an identical volume of peptide solution dissolved in TFE was added. 76 Then, the samples were vortexed and lyophilized overnight. CD spectra were recorded at a peptide concentration of 8 μM and at a lipid final concentration of 100 μM.…”
Section: Methodsmentioning
confidence: 99%